2014
DOI: 10.1002/jhet.2212
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Ethyl (substituted)phenyl‐4‐oxothiazolidin‐3‐yl)‐1‐ethyl‐4‐oxo‐1,4‐dihydroquinoline‐3‐Carboxylates as Potential Anticancer Agents

Abstract: A series of ethyl (substituted)phenyl-4-oxothiazolidin-3-yl)-1-ethyl-4-oxo-1,4-dihydroquinoline-3-carboxylates (7a-g) has been prepared from reactions between aminoquinolones 6 with arenealdehydes and mercaptoacetic acid. The critical intermediates, 6a and 6b, were obtained from appropriate amines by a sequence of steps involving (i) reaction with diethylethoxymethylenemalonate, (ii) thermal cyclization in diphenyl ether, (iii) ethylation and (iv) Pd/C catalyzed reduction. New compounds 7a-g were fully identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Purification of the crude product was performed by column chromatography (silica gel, hexane/EtOAc) affording the pure 1-(3-Amino-2,4-dihydroxyphenyl)-1-ethanone in 72% yield (0.92 g, 4.7 mmol). This compound (1.0 g, 5.0 mmol) was poured into a hydrogenation flask, followed by the addition of Pt/C (0.1 g, 10 mol %), and the mixture was subjected to hydrogenation at 28 atm (420 psi) at 50 °C . The reaction was monitored by TLC until total conversion of the starting material was achieved.…”
Section: Methodsmentioning
confidence: 99%
“…Purification of the crude product was performed by column chromatography (silica gel, hexane/EtOAc) affording the pure 1-(3-Amino-2,4-dihydroxyphenyl)-1-ethanone in 72% yield (0.92 g, 4.7 mmol). This compound (1.0 g, 5.0 mmol) was poured into a hydrogenation flask, followed by the addition of Pt/C (0.1 g, 10 mol %), and the mixture was subjected to hydrogenation at 28 atm (420 psi) at 50 °C . The reaction was monitored by TLC until total conversion of the starting material was achieved.…”
Section: Methodsmentioning
confidence: 99%
“…Also, it was reported that some quinoline analogues bearing thiazolidine moiety have apoptotic activity and acts as kinase inhibitors for the treatment of colorectal cancer (Bathula et al, 2016; Finiuk et al, 2017; Kobylinska et al, 2019; Senkiv et al, 2016; Zhang et al, 2014; Zhou et al, 2021). Attaching thiazole to quinoline nucleus is expected to increase the overall compound activity (Aly et al, 2020; Andreani et al, 2005; Erguc et al, 2018; Facchinetti et al, 2015; Ghorab et al, 2016); this encouraged us to test the anticancer activity of previously synthesized derivatives (Amer et al, 2018) through apoptosis induction.…”
Section: Introductionmentioning
confidence: 99%